2020
DOI: 10.1523/jneurosci.0951-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Calcineurin in Schwann Cells Does Not Affect Developmental Myelination, But Reduces Autophagy and Delays Myelin Clearance after Peripheral Nerve Injury

Abstract: In the PNS, myelination occurs postnatally when Schwann cells (SCs) contact axons. Axonal factors, such as Neuregulin-1 Type III, trigger promyelinating signals that upregulate myelin genes. Neuregulin-1 Type III has been proposed to activate calcineurin signaling in immature SCs to initiate differentiation and myelination. However, little is known about the role of calcineurin in promyelinating SCs after birth. By creating a SC conditional KO of calcineurin B (CnB scko), we assessed the effects of CnB ablatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 60 publications
6
23
0
Order By: Relevance
“…4E,G). This is consistent with recent observations from our laboratory showing that KROX20 expression is independent of calcineurin activity in mature myelinating Schwann cells (Reed et al, 2020).…”
Section: Calcineurin Signaling Is High In S63del Nervessupporting
confidence: 94%
See 1 more Smart Citation
“…4E,G). This is consistent with recent observations from our laboratory showing that KROX20 expression is independent of calcineurin activity in mature myelinating Schwann cells (Reed et al, 2020).…”
Section: Calcineurin Signaling Is High In S63del Nervessupporting
confidence: 94%
“…In immature Schwann cells, activation of calcineurin induces the expression of the promyelinating transcription factor Early Growth Response 2 (EGR2/ KROX20), thus representing an ideal candidate to be disrupted by P-PERK in a demyelinating neuropathy with an active UPR (Kao et al, 2009). However, our recent data have demonstrated that selective deletion of calcineurin in myelinating Schwann cells has no effect on KROX20 expression or myelin production, but rather limits myelin clearance after injury (Reed et al, 2020). We thus explored the hypothesis that P-PERK interacts and modulates calcineurin activity in S63del Schwann cells, thus contributing to the demyelinating neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, conducted first in zebrafish and later in mice, have shown that Schwann cells participate in the breakup of the axon during the process of axon degeneration [65][66][67][68][69][70]. This process involves the formation of constricting actomyosin spheres and partially requires placental growth factor signalling from the axon, the vascular endothelial growth factor receptor (VEGFR) on Schwann cells, activation of mechanistic target of rapamycin (mTOR) and potentially calcineurin B in Schwann cells [65,69,71,72]. Furthermore, it has recently been shown that Schwann cells upregulate glycolysis after injury and that this process may actually help to protect axons for a short period after injury prior to axon degeneration [65].…”
Section: The Schwann Cell Response To Nerve Injurymentioning
confidence: 99%
“…The role of TFEB in the modulation of cancer peripheral nervous system is mostly speculative. Of note, TFEB has been demonstrated to regulate the formation of myelin [141,142], which is instrumental in perineural invasion and tumor spread through this way [114,143].…”
Section: Accepted Articlementioning
confidence: 99%